Risk Factor Related to Mortality of Diabetic Ketoacidosis Patients in Dr. Soetomo General Hospital Surabaya - Alviano Satria Wibawa; Hermina Novida; Muhammad Faizi; Deasy Ardiany (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2020)
Introduction: Diabetic ketoacidosis (DKA) is a complication of diabetes mellitus which has a high risk of mortality. Mortality in DKA patients in developed countries is less than 5%, some other sources mention 5-10%, 2-10%, or 9-10%. Mortality events at clinics with simple facilities and elderly patients can reach 25-50%. The mortality rate of DKA patients is generally higher in infection conditions, especially in developing countries and in septic patients. Several factors such as age, sex, and high blood glucose can increase mortality risk of DKA patients. Other risk factors such as history of discontinued insulin therapy, impaired bicarbonate levels, pH, and increased leukocytes of DKA patients due to infection, abnormal albumin levels, electrolyte disturbances, and Serum Creatinine (SK) were thought to affect mortality of DKA patients. The purpose of this study was to determine the risk factors associated with mortality of DKA patients in Dr. Soetomo General Hospital Surabaya. Methods: The method used in this study was observational analytic involving 63 adult patients diagnosed with DKA with analysis using Chi-Square test. Results: From 63 patients included in this study, 37 patients diagnosed with DKA died and 26 patients lived. In a multivariate analysis, DKA severity with p = 0.001 (p < 0.005) was identified as having a relationship with mortality of DKA patients Dr. Soetomo General Hospital Surabaya. Conclusion: Severity is the only risk factor associated with mortality of DKA patients in Dr. Soetomo General Hospital Surabaya.